A Practical Study Of The Tensile Strength Of Yarns In The Process Of Adding And Winding To Obtain Baked Yarn Of A Complex Structure (Eurasian Journal of Engineering and Technology, 2024)
In this article, the tensile strength of the yarns during the process of adding and winding to obtain a baked yarn with a complex structure was theoretically analyzed. The analysis of the field research shows that the expansion of the assortment of textile yarns, the production of spun yarns by joining two or more single yarns at the same tension, the yarn at the same tension during the winding process, the further improvement of the product and the provision of an efficient process in the technological system have been determined. By using it, it is possible to implement more technological processes at high speed to obtain better quality products, the results of research work and a comparative analysis were developed. Based on these analyses, recommendations were made